1997
DOI: 10.1089/dna.1997.16.1357
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Novel Neuropeptide Y Receptor Subtype in the Zebrafish

Abstract: Neuropeptide Y (NPY), peptide YY (PYY), and pancreatic polypeptide (PP) form a family of structurally related peptides. As we have previously isolated clones for NPY and PYY from the zebrafish (Danio rerio), we wished to clone the receptors for these peptides to allow correlation of ligand and receptor distribution. We describe here the cloning and functional expression of a receptor with equally high identity to the NPY-Y1 receptor as to the recently cloned Y4/PP1 and Y6 receptors with an overall amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…For example, our WU-BLAST analysis failed to distinguish between human ACTB (on Hsa1), ACTC (on Hsa15), and ACTG1 (on Hsa17) as the most likely ortholog for zebrafish bact2 (Kelly and Reversade 1997). The map position for bact2 on LG3 (Geisler et al 1999) near Pyy (on Hsa17; Lundell et al 1997) argues that bact2 is the zebrafish ortholog for ACTG1, rather than ACTB or ACTC. Similarly, WU-BLAST analysis fails to unambigu- .…”
Section: Resultsmentioning
confidence: 89%
“…For example, our WU-BLAST analysis failed to distinguish between human ACTB (on Hsa1), ACTC (on Hsa15), and ACTG1 (on Hsa17) as the most likely ortholog for zebrafish bact2 (Kelly and Reversade 1997). The map position for bact2 on LG3 (Geisler et al 1999) near Pyy (on Hsa17; Lundell et al 1997) argues that bact2 is the zebrafish ortholog for ACTG1, rather than ACTB or ACTC. Similarly, WU-BLAST analysis fails to unambigu- .…”
Section: Resultsmentioning
confidence: 89%
“…A preliminary version of a part of this study was previously published (Salaneck et al, 2005) before the zebrafish Y 1 gene was identified. Also, we wanted to better understand the evolutionary history of the two subtypes called Y 8 that have been found in euteleosts, namely Y 8a and Y 8b , initially called Yc and Yb, respectively (Lundell et al, 1997;Ringvall et al, 1997). A single Y 8 gene exists in frogs, mammals and chicken.…”
Section: Discussionmentioning
confidence: 99%
“…The Acba Y 1 sequence was extended in the 5′ direction using the inverse PCR technique described earlier (Salaneck et al, 2003). BLAST searches using the human NPY receptor sequences and previously identified Danio rerio sequences (Lundell et al, 1997;Ringvall et al, 1997;Starback et al, 1999;Fredriksson et al, 2004;Fredriksson et al, 2006) were used to make a preliminary survey of the NPY receptor repertoire in the fully sequenced genomes of Danio rerio, Oryzias latipes, Tetraodon nigroviridis, Takifugu rubribes and Gasterosteus aculeatus (see Supplementary Table 2). In D. rerio the sequence for Y 1 was obtained by PCR with specific primers based on the predicted coding sequence of the Y 1 sequence found in the zebrafish genome database and cloned into TOPO vector and sequenced as described above.…”
Section: Pcr and Cloningmentioning
confidence: 99%
“…Amphibians have all of the mammalian subtypes and in addition Y7, as in chicken, and also the Y1-subfamily receptor previously described in fish, namely Y8, previously called Yb [92]. Only the Y1, Y2 and Y7 sequences have yet been published [93,94] and work is in progress to characterise all receptors.…”
Section: Vertebrate Y Receptorsmentioning
confidence: 99%
“…Prior to the initiation of these genome sequencing projects three Y1-like receptors had been cloned from zebrafish, but did not seem to represent orthologues to any of the mammalian Y1, Y4 or Y6 genes. These fish sequences were therefore tentatively regarded as novel genes and given distinct gene names, namely Ya, Yb and Yc [92,95,96]. As additional Y receptor sequences were reported, the relationships of these genes have become clearer.…”
Section: Figure 4 Proposed Gene Duplication Scheme For the Y Receptormentioning
confidence: 99%